2019
DOI: 10.14513/actatechjaur.v12.n3.505
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Study of a Nonlinear Semi-Active Suspension System

Abstract: In this paper the OAT (one-at-a-time) sensitivity analysis of a nonlinear semi-active suspension system is carried out with numerical simulation. A specific property of the system is chosen for measure sensitivity, which can be calculated with numerical simulations easily. Both the sensitivity of the system and the input parameters were examined. The degree of sensitivity was measured with a sensitivity index and based on it sensitivity Fuzzy-sets were established. A simple method to reduce sensitivity of a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…For effective study it is also important to select the proper variable or property to measure sensitivity. In this paper different output variables of nonlinear vibration systems are tested with a Fuzzy-set based OaT sensitivity study method developed in [23]. The aim of the research is to develop a widely and easily useable numerical examination method of nonlinear systems with special focus on mechanical and mechatronics applications and to make the designdevelopment process more efficient.…”
Section: Fig 1 Parameter Sensitivity Study Methods (Based On [20])mentioning
confidence: 99%
See 3 more Smart Citations
“…For effective study it is also important to select the proper variable or property to measure sensitivity. In this paper different output variables of nonlinear vibration systems are tested with a Fuzzy-set based OaT sensitivity study method developed in [23]. The aim of the research is to develop a widely and easily useable numerical examination method of nonlinear systems with special focus on mechanical and mechatronics applications and to make the designdevelopment process more efficient.…”
Section: Fig 1 Parameter Sensitivity Study Methods (Based On [20])mentioning
confidence: 99%
“…The detailed sensitivity study of a semi-active suspension system using the RMS of acceleration can be found in [23]. The parameters of the current study are based on that model, only the excitation signal was different.…”
Section: Using the Rms Of Accelerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously the One-at-a-Time (OAT) parameter sensitivity study of a Duffing-type semi-active suspension system was carried out [17], where it was observed that the damping coefficient is the most sensitive parameter. A simple output parameter was chosen and based on it sensitivity Fuzzy sets were established to reflect the degree of sensitivity.…”
Section: Introductionmentioning
confidence: 99%